ДИНАМИКА ТЯЖЕЛЫХ МЕТАЛЛОВ И МЕТАЛЛОИДОВ В ОРОШАЕМЫХ ПОЧВАХ (Scientific journal of the Fergana State University, 2026)
This article examines the quantitative composition, distribution dynamics, and geochemical properties of heavy metals and metalloids in irrigated soils. The study determines the migration, accumulation, and Clarke values ​​of heavy metals and metalloids in the genetic horizons of light gray soils with different irrigation levels, and develops background values. Furthermore, the migration dynamics of heavy metals and metalloids in soil horizons are revealed using geochemical spectra.